Penerapan Arsitektur Kontemporer Pada Perancangan Akademi Sepak Bola Rans Cilegon FC di Jakarta - Ali Nugraha; Dody Kurniawan; Sri Kurniasih (MAESTRO, 2022)
Building the Foundation of Indonesian Football with a Football School is inevitable if Indonesia wants to talk a lot in the Asian Football caste and the world. The Football School as a motor for producing young players should receive priority in the various policies issued by the PSSI Federation, both at the national and regional levels. The proliferation of soccer schools is a development that should be appreciated, because it shows that the public has realized the spearhead of the revival of Indonesian football. In an effort to build a Football Academy, it is necessary to have support from various parties for the rise of Indonesian football.